Working memory capacity, reading proficiency, and the processing of verbal and pictorial information in English as a foreign language reading - Woelfer, Sidnei Werner (2019)
This study investigates interplays among working memory capacity (WMC), reading proficiency, and the processing of verbal and pictorial information in English as a foreign language (EFL) reading. Participants were sixty Brazilian public-school students aged 15-17 years old (M = 16.3, SD.= 64). Instruments comprised a background questionnaire, an EFL reading proficiency test, a WMC test, a reading comprehension test, and a retrospective questionnaire. Quantitative and qualitative analyses revealed a positive correlation between the independent variables (i.e., EFL reading proficiency and WMC), as well as a significant association between each of the independent variables and the dependent variable (i.e., reading comprehension). Results indicated that: (1) WMC limitations appear to constrain the processing of non-illustrated expository texts; (2) low EFL reading proficiency may hamper the efficiency of pictorial information processing; and (3) WMC limitations in the processing of pictorial information seem to be compensated by the activation of background knowledge.